Analiza rentowności banku w aspekcie ryzyka - Kopiński, Adam (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents the following triad: profitability - risk - development, where we find the traditional conflict between high profitability of bank activity, due to development, but at the expense of bank risk. Subsequently the paper discusses particular types of bank risk, such as financial liquidity risk, interest rate risk, credit risk and exchange rate risk as well as their influence on financial values which determine bank profitability. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 132-137